Variability in virulence of Beauveria spp. soil isolates against Ostrinia nubilalis. (7th August 2020) - Medo, Juraj; Medová, Janka; Michalko, Jaroslav; Cagáň, Ľudovít
Abstract: European corn borer ( Ostrinia nubilalis ) is an important maize pest which is treated mainly by synthetic pesticides with many negative effects for ecosystem and human health. Soil borne entomopathogenic fungi of species belonging to Beauveria genus may provide an alternative strategy for biological control of this pest. In this article, we report results of virulence testing of 46 soil isolates of Beauveria spp. against O. nubilalis in relation to isolates origin and haplotype. All strains were collected from soil using Galleria mellonella bait method. Conidia suspension with concentration 10 7 conidia in ml was used for virulence test against 4th instar larvae of O. nubilalis at temperature 25°C. After 14 days, mortality of larvae was in the range 34%–96%. Median lethal time LT50 was estimated to 5.5–21.3 days. Mortality was not in relation to habitat or any other environmental parameter of sites where isolates came from. Differences among species were insignificant. Isolates were divided into 8 genetic lineages and 14 haplotypes using sequencing of ITS and Bloc nuclear regions. None of the lineages showed higher mortality than others. Despite more or less virulent isolates being found in each lineage, the three most virulent isolates belonged to the same lineage Beauveria bassiana A3. The four most virulent isolates were compared to commercial isolate GHA to assess medium lethal concentration. LC50 were estimated in range 7.5 × 10 4 to 9.5 × 10 5 . Three of the four isolates showed equal or greater efficiency than strain GHA.